Lessons learned from the virus indexing of Musa germplasm: insights from a multiyear collaboration - Clerck, Caroline de; Crew, K.S.; Houwe, Ines van den; McMichael, L.; Berhal, C.; Lassois, L.; Haissam Jijakli, M.; Roux, N.; Thomas, J.; Massart, S. (Wiley, 2017)
The Bioversity International Transit Center (ITC) for banana hosts more than 1500 accessions largely covering the genetic diversity of the genus Musa. Its objective is to conserve this genetic diversity and to supply plant materials to users worldwide. All the Musa accessions must be tested for virus presence and, if infected, virus elimination must be attempted, to enable the supply of virus‐free plant material. An international collaborative effort launched under the auspices of Bioversity International (2007–2013) finally led to the implementation of a two‐step process to test the accessions. The first step, called pre‐indexing, involved only molecular tests and was designed as a pre‐screen of new germplasm lines or existing accessions to reduce the need for post‐entry virus therapy and repeated virus indexing. The second step, called full indexing, was performed on either older existing accessions or newer accessions which tested negative during pre‐indexing, and involved molecular tests, transmission electron microscopy (TEM) and symptom observation. In total, 270 germplasm lines (434 samples) were pre‐indexed; while full indexing was carried out on 243 accessions (68 of which had been pre‐indexed). A significant proportion of the samples tested during pre‐indexing was infected with at least one virus (68%), showing the utility of this early pre‐screening step. Banana streak OL virus and Banana mild mosaic virus were the most commonly detected viruses during both pre‐ and full indexing. For 22 accessions, viral particles were observed by TEM in full indexing while the molecular tests were negative, underlining the importance of combining various detection techniques. After full indexing, viruses were not detected in 166 accessions, which were then released for international distribution from the ITC. This publication exemplifies how the practical application of diagnostic protocols can raise fundamental questions related to their appropriate use in routine practice and the need for their continuous monitoring and improvement after their first publication.